EFFECT OF DIFFERENT LEVELS OF OLEOBIOTEC® ON PRODUCTION PERFORMANCE AND EGG QUALITY TRAITS IN JAPANESE QUAIL. - Mustafa, Merkhan M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was conducted at the Animal |Production Sciences, College of Agricultural Engineering Science, University of Duhok to estimate the effect of different levels of oleobiotec on the production performance, egg quality of Japanese quail. A total of 105 Japanese quail 17 weeks of age obtained from a local farm and distributed into five treatments with three replicate for each one had (7 quail). Different doses of oleobiotec significantly (P ≤ 0.05) improved egg production, egg weight, and egg mass, fed conversion ratio and egg weight uniformity percentage. Concerning egg haugh unit significantly improved (P<0.05) by using oleobiotec while, other egg quality did not influenced with different level of oleobiotec.